Addition of Induction or Consolidation Chemotherapy in Definitive Concurrent Chemoradiotherapy Versus Concurrent Chemoradiotherapy Alone for Patients With Unresectable Esophageal Cancer: A Systematic Review and Meta-Analysis - Wang, Jianing; Xiao, Linlin; Wang, Shuai; Pang, Qingsong; Wang, Jun (Frontiers in Oncology, 2021)
Background: Concurrent chemoradiotherapy (CCRT) have become the standard of care in esophageal carcinoma patients who are not surgical candidates. The efficacy of induction chemotherapy (IC) or consolidation chemotherapy (CCT) for unresectable esophageal cancer (EC) treated with CCRT is unclear. We performed a systematic review and meta-analysis of published papers to evaluate the potential benefit of IC or CCT for patients with EC. Methods: Eligible studies of IC followed by CCRT (IC-CCRT) versus CCRT alone or CCRT followed by CCT (CCRT-CCT) versus CCRT alone were retrieved through extensive searches of the PubMed, Science Direct, Embase, and Cochrane library databases from the establishment of the database to July 31, 2021. Data such as one-, two-, three- and five-year overall survival (OS), local recurrence rate (LRR) and distant metastasis rate (DMR) were collected for meta-analysis to evaluate the efficacy of IC/CCT. Results: There were 4 studies of IC-CCRT versus CCRT including 836 EC patients and 6 studies of CCRT-CCT versus CCRT including1339 patients with esophageal squamous cell carcinoma (ESCC) were finally identified in our analysis. Both IC-CCRT group (HR 0.446, 95% CI 0.286-0.693; P<0.001) and CCRT-CCT group (HR0.542, 95%CI 0.410-0.716; P＜0.001) exhibited statistically significant improvement in one-year OS rate compared to CCRT, while the two-year OS rate of IC-CCRT (HR 0.803, 95% CI 0.589-1.095; P=0.166) or CCRT-CCT (HR 0.783, 95% CI0.600-1.022; P=0.072) was similar with CCRT. And the three-year OS rate between IC-CCRT and CCRT was similar (HR 1.065, 95%CI 0.789-1.439; P=0.680). However, comparing with CCRT alone, CCRT-CCT group had lower DMR (OR 1.562, 95%CI 1.090-2.240; P=0.015) and higher three-year OS rate (HR 0.786, 95%CI 0.625-0.987; P=0.039). Besides, no differences were observed between two groups of CCRT-CCT and CCRT in five-year OS rate (HR 0.923, 95%CI 0.706-1.205; P=0.555) and LRR (OR 0.899,95%CI 0.686-1.179; P=0.441). Conclusion: The study revealed the short-time survival benefit of additional IC or CCT compared to CCRT alone for patients with unresectable EC, and CCRT followed by CCT could significantly reduce the risk of distant metastases.